2020
DOI: 10.3390/ijms22010362
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Modulates Intestinal Microbiota in Inflammatory Bowel Diseases

Abstract: Inflammatory bowel disease (IBD) is a chronic inflammation of the gastrointestinal tract (GIT), including Crohn’s disease (CD) and ulcerative colitis (UC), which differ in the location and lesion extensions. Both diseases are associated with microbiota dysbiosis, with a reduced population of butyrate-producing species, abnormal inflammatory response, and micronutrient deficiency (e.g., vitamin D hypovitaminosis). Vitamin D (VitD) is involved in immune cell differentiation, gut microbiota modulation, gene trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 162 publications
(106 reference statements)
3
100
0
5
Order By: Relevance
“…There are reports that vitamin D supplementation in pediatric patients with IBD improved bone mineral density and muscle strength [ 113 ], but data in adult patients with IBD are lacking. Vitamin D supplementation in patients with IBD also improves dysbiosis [ 114 ]. VDRs are involved in the regulation of T cell and Paneth cell function and regulate the release of antimicrobial peptides in gut bacteria–host interactions [ 114 ].…”
Section: Intervention For Patients With Ibd and Sarcopeniamentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports that vitamin D supplementation in pediatric patients with IBD improved bone mineral density and muscle strength [ 113 ], but data in adult patients with IBD are lacking. Vitamin D supplementation in patients with IBD also improves dysbiosis [ 114 ]. VDRs are involved in the regulation of T cell and Paneth cell function and regulate the release of antimicrobial peptides in gut bacteria–host interactions [ 114 ].…”
Section: Intervention For Patients With Ibd and Sarcopeniamentioning
confidence: 99%
“…Vitamin D supplementation in patients with IBD also improves dysbiosis [ 114 ]. VDRs are involved in the regulation of T cell and Paneth cell function and regulate the release of antimicrobial peptides in gut bacteria–host interactions [ 114 ]. On the other hand, mucosal healing and disease remission in patients with IBD can significantly improve oral feeding and nutritional status, and prevent muscle loss.…”
Section: Intervention For Patients With Ibd and Sarcopeniamentioning
confidence: 99%
“…The benefits of the gut microbiota to the host’s physiology include nutrition, immune development, and host defense [ 126 ]. Increasing evidence has shown that some dietary nutrients from environmental factors and PRRs-mediated signaling pathways from host modulate the composition and metabolism of gut microbiota, which influence IBD onset [ 127 , 128 , 129 , 130 , 131 , 132 , 133 ]. Supplementation with 20 mg/kg melatonin (MT) by intraperitoneal injection could downregulate the colon ROS levels, and inhibit the changes of the intestinal microbiota and TLR2/TLR4 activities induced by restraint stress, which together mitigate psychological stress-induced colonic inflammatory responses [ 134 ].…”
Section: Therapeutic Targets For Suppressing Inflammatory Diseases Based On the Correlations Between Ros Regulation And Prr-mediated Signmentioning
confidence: 99%
“…In a birth cohort study, prenatal and cord blood vitamin D levels were associated with early life (up to 1 month) gut microbiota [ 36 ]. Recently, a review highlighted the therapeutic potential of vitamin D/VDR in the gut microbiota modulation and anti-inflammatory effects in IBD [ 38 ].…”
Section: Vitamin D and Microbiota: Human Studiesmentioning
confidence: 99%